Policies to Eliminate Poverty Rate in Indonesia - Afandi, Akhsyim; Wahyuni, Dwi; Sriyana, Jaka (International Journal of Economics and Financial Issues, 2017)
This study aims to analyze the factors that influence the poverty rate in Indonesia in the period of 1981-2013. This research uses Error Correction Model to estimate the empirical poverty model. The findings may be explained as follows: Economic growth does not influence the poverty reduction; meanwhile inflation has a significant positive effect on the poverty level. Foreign direct investment as an indicator of economy openness has a negative impact on the poverty. In addition, Gini ratio as an income equality measurement has no significant influence on the poverty level. These findings show that the poverty level depends on macroeconomic instability especially price level. Higher inflation rate leads to higher rate of poverty in the country. Furthermore, the central government should keep the monetary sector using tight monetary policy to eliminate the poverty level. Keywords: Gross Domestic Product, investment, inflation, Gini ratio, poverty. JEL Classifications: E01, E31, I32